"Fool me once, shame on you… then, I learn." An examination of information disclosure in social networking sites. (June 2018) - Osatuyi, Babajide; Passerini, Katia; Ravarini, Aurelio; Grandhi, Sukeshini A.
Abstract: This study investigates factors that affect user decisions on which information to share, and specifically whether and how to disclose sensitive personal information, when using social networking sites (SNSs). The determinants of personal information disclosure (self-disclosure) are identified using a framework that combines communication privacy management and social penetration theories. Communication privacy management theory is applied to identify which rules guide users' sharing of personal information. Social penetration theory is used to understand personal information disclosure approaches—deep and shallow—that people employ on SNSs. Structural equation modeling was used to analyze data from 315 Facebook users who were also undergraduate students. Results show that individuals self-disclose more on SNSs when they know how to coordinate disclosure boundaries, and particularly when they have learned from prior privacy infringements. While types of relationships are important in determining self-disclosure approaches, SNSs users who have experienced a privacy breach follow different privacy coordination rules compared with those who have not experienced such an incident. Our results present an interesting twist in which the "fooled once" users show higher levels of information sharing at all levels. These users have learned their lessons and their way through privacy management options, eventually leading to a higher self-disclosure. Highlights: Individuals self-disclose more on SNSs when they know how to manage disclosure. Self-disclose is higher on SNSs when users have learned from prior privacy infringements. Individuals use two self-disclosure approaches on SNS, deep and shallow disclosures. Shallow disclosure has a stronger relationship with self-disclosure continuance than deep disclosure.